Literature and Analytics: Changing Aesthetics in the Age of Big Data: Exploring the Impact of Big Data on Language and Literature (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Language is a faculty that differentiates Homo sapiens from other animals on Earth. It is a gift that evolution brought to humans. All human societies have language that can communicate their experiences fully. The invention of printing resulted in the universalization of knowledge after the European Renaissance. The growth of science, especially after Darwin, has shattered traditional philosophical and religious ideologies. Science has come to the centre of everything and revolutionized human values and progress. The revolution in the field of communication technology assisted by the English languagehas changed the modes of communication and replaced traditional means. With the advent of information technology, every aspect of Homo sapiens’ life has been convertedto data. Technology has enabled us to measure an ever-increasing volume, variety, velocity and veracity of data in an age of ‘big data’. The possibilities of billions of people connected by mobile devices, with unprecedented processing power, storage capacity and access to knowledge are unlimited. E-readers and tablet computers have changed not only the way of reading but also the way of composition. The communication revolution is going to transform the way language is used and literature is experienced. It is a monumental shift that is going to change the very definition of language and it is a progressive move in the creation and publication of literature.